Evaluation of Waterpark Performance Using Distance Measure on Pythagorean Fuzzy Sets (Jurnal Matematika, Statistika dan Komputasi, 2026)
The rapid growth of the tourism industry, particularly in waterparks, necessitates a comprehensive evaluation to enhance customer satisfaction and competitiveness. This study aims to evaluate the performance of waterparks in Manado City using the Distance Measure method on Pythagorean Fuzzy Sets (PFS). Data were collected through questionnaires from 100 visitors across four waterparks: Lomban, Mercy, Citraland, and Paradise. The findings reveal that Citraland Waterpark achieved the highest relative similarity score of 0.5234, followed closely by Lomban Waterpark at 0.51990 and Mercy Waterpark at 0.51949, while Paradise Waterpark ranked last with a score of 0.4762. Further analysis indicates that Citraland Waterpark excels in nearly all evaluation attributes, including service quality and cleanliness. This research demonstrates the effectiveness of applying Distance Measure on PFS in addressing uncertainties in subjective customer assessments, providing valuable insights for waterpark managers to enhance service quality. Future research is recommended to expand the study to include additional waterparks and evaluation attributes for a more comprehensive analysis.
Keywords: Waterpark; Pythagorean Fuzzy Set; Distance Measure; Performance Evaluation